Multiphase CO2-dependent photosynthesis in marine diatoms - Shimakawa, Ginga; Matsuda, Yusuke (Frontiers in Photobiology, 2025)
Diatoms, one of the most ubiquitous phytoplankton in the oceans, have evolved a pyrenoid-based CO2-concentrating mechanism (CCM) to utilize limited CO2 in seawater for photosynthesis. Recent proteomics analyses and molecular biological tools have deepened our understanding of the molecular mechanisms involved in diatom chloroplast architecture and the CCM. Here, we provide an update to our knowledge of the processes involved in high affinity photosynthesis for dissolved inorganic carbon (DIC) in diatoms. Based on the phenotype of genome-edited mutants, we propose a model of the diatom CCM composed of four phases of CO2-dependent photosynthesis at (I) less than 0.1 mM, (II) 0.1–2 mM, (III) 2–10 mM, and (IV) more than 10 mM of DIC concentrations, in which the rate-determining steps are the capture of unfixed CO2 in the chloroplast stroma at Phases I and II, the evolution of CO2 in the pyrenoid-penetrating thylakoid lumen at Phase III, and DIC transport to the stroma at Phase IV. Under natural seawater containing 2 mM DIC mainly in the form of HCO3−, the photosynthesis of marine diatoms is likely primarily in Phase III, shifting to Phase II when available CO2 is limited.